Animals and Animality in Primo Levi's Work - Benvegnù, Damiano (The Palgrave Macmillan Animal Ethics Series, 2018)
Situated at the intersection of animal studies and literary theory, this book explores the remarkable and subtly pervasive web of animal imagery, metaphors, and concepts in the work of the Jewish-Italian writer, chemist, and Holocaust survivor Primo Levi (1919-1987). Relatively unexamined by scholars, the complex and extensive animal imagery Levi employed in his literary works offers new insights into the aesthetical and ethical function of testimony, as well as an original perspective on contemporary debates surrounding human-animal relationships and posthumanism. The three main sections that compose the book mirror Levi's approach to non-human animals and animality: from an unquestionable bio-ethical origin ("Suffering"); through an investigation of the relationships between writing, technology, and animality ("Techne"); to then enter upon a creative intellectual project in which literary animals both counterbalance the inevitable suffering of all creatures, and suggest a transformative image of interspecific community ("Creation").